2011
DOI: 10.1002/jbmr.370
|View full text |Cite
|
Sign up to set email alerts
|

Circulating osteogenic cells: Implications for injury, repair, and regeneration

Abstract: The aim of this review is to provide a critical reading of recent literature pertaining to the presence of circulating, fluid-phase osteoblastic cells and their possible contribution to bone formation. We have termed this group of cells collectively as circulating osteogenic precursor (COP) cells. We present evidence for their existence, methods used for their isolation and identification, possible physiological and pathophysiological roles, cellular origins, and possible mechanisms for their migration to targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 94 publications
2
57
0
Order By: Relevance
“…Several studies indicate that stem cells and osteoblast precursors exist in circulation (31). It is possible that bone marrow disruption due to bone injury may induce egress of MSCs and HSCs into circulation (10).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies indicate that stem cells and osteoblast precursors exist in circulation (31). It is possible that bone marrow disruption due to bone injury may induce egress of MSCs and HSCs into circulation (10).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that fucoidan can be used in bone health supplements and as an additive for biomaterial-based scaffolds to promote bone regeneration. Efficient bone regeneration and repair is mediated by directed cell migration of osteoblasts to sites in need of bone formation (Pignolo & Kassem 2011;Dirckx et al 2013;Meng & Xie 2014;Song & Park 2014). Some controversial effects of fucoidan on cell migration have been reported in several types of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…1). Osteogenic cells appear to circulate at low levels [30,47], but the proportion of circulating osteogenic stem or progenitor cells can be enhanced through mobilization, which is defined as forced egress of stem/progenitor cells from their niche(s), One or more of the authors (DRS, ASV, KWC) has received funding from the Musculoskeletal Transplant Foundation (Edison, NJ, USA) for support of this work. All ICMJE Conflict of Interest Forms for authors and Clinical Orthopaedics and Related Research editors and board members are on file with the publication and can be viewed on request.…”
Section: Introductionmentioning
confidence: 99%